PENINGKATAN HASIL BELAJAR AKUNTANSI MENGGUNAKAN STUDENT TEAMS ACHIEVMENT DIVISION - Fitri Nurlaili; Idmi Idmi; Haslinda Haslinda (FKIP, Universitas Banten Jaya, 2018)
The purpose of this research were to improve the learning outcomes and their activities in accounting learning with cooperative learning model Student Teams Achievment Division (STAD) in grade XI AK students at SMK Madinatul Hadid Cilegon.This research used Classroom Action Research (CAR) consists of two cycles. Each cycle consisted of four stages: planning, acting, observing, and reflecting. The research subjects were the students in XI AK in SMK Madinatul Hadid Cilegon with 21 students and the teacher as the collaborator team.The result of this research showed that the application of STAD learning model could improve the student activity from cycle I was 39% up to 45%, there was increasing 6%. While in cycle II, the activity became 66% in first meeting and increased to 82% in second meeting, there was increasing 16%. In cognitive aspect, the average scores of pretest was 57. In cycle I, after post test the score 72. In the second cycle, the average value increased to 85. Students, who had score above the KKM was 47% in first cycle while in the second cycle 100% of student could reach the KKM.